(untitled) (Journal of Contemporary Philology, 2022)
This study aims to show how different political leaders combine metaphor use with the populist sentiment in their response to the COVID-19 pandemic. To analyse the populist nature of the recurrent metaphor use, 17 leaders’ national lockdown speeches from different countries were collected and analysed within the theoretical framework of critical metaphor studies and frame semantics. Procedurally, metaphors in the collected speeches were identified by applying Pragglejaz Group’s MIP (2007) and coded into thematic categories via NVivo 12.0. Overall, four thematic codes (470 metaphorical expressions) were established, and their content analysis has demonstrated specific differences in the leadership style with regard to populism. It has been clarified that the male political leaders tend to prioritise the arousal of negative emotions discursively expressed through the antagonism between the collective Self and the collective Other (the virus), and a heightened sense of unpredictable (economic) future. By contrast, the female political leaders overwhelmingly focused on their affinity with the collective Self in the context of social accountability and mutual trust.